Association Between the Patterns of Five Unhealthy Behaviors and Suicidal Behaviors Among Adolescents in Six Provinces of China - Guo, Chunyu; Xue, Yanni; Xia, Zhengmei; Cui, Yingying; Hu, Jie; Huang, Xuexue; Wan, Yuhui; Fang, Jun; Zhang, Shichen (Frontiers in Psychiatry, 2022)
Background: In adolescents, multiple unhealthy behaviors occur frequently together which are likely to be associated with suicide behaviors (SBs), increasing the risk of suicide. This study aimed to clarify the potential patterns of unhealthy behaviors in Chinese adolescents, and examine the associations between different patterns of unhealthy behaviors and SBs. Methods: A total of 22,628 middle school students were enrolled in this study. Self-reported unhealthy behaviors and SBs were investigated by questionnaires. Latent class analysis (LCA) was performed based on five unhealthy behaviors [smoking, alcohol use (AU), diet pills use (DPU), screen time (ST), problematic mobile phone use (PMPU)]. Multivariate logistic regressions were used to examine the associations between the different patterns of unhealthy behaviors and SBs. Results: Four subgroups of unhealthy behaviors were identified by LCA, including high-risk class (smoking/AU/DPU/PMPU/ST), moderate-risk class 1 (DPU/PMPU), moderate risk class 2 (smoking/AU/ST), and low-risk class. Compared with the low-risk class, all of the moderate-risk class 1, moderate-risk class 2 and high-risk class had higher risks of suicide ideation, suicide plan, and suicide attempt. Conclusions: These findings suggested that the patterns of unhealthy behaviors were related to SBs in Chinese adolescents. Accordingly, considerations of different classes of unhealthy behaviors may be essential for developing effective preventive programs.